624 A PHASE III STUDY ON NEOADJUVANT TORIPALIMAB PLUS CHEMOTHERAPY VERSUS NEOADJUVANT CHEMOTHERAPY FOR LOCALLY RESECTABLE ESOPHAGEAL SQUAMOUS CELL CARCINOMA. (17th September 2021) - Zheng, Yan; Zhang, Jiangong; Xing, Wenqun
Abstract: : In recent years, immune checkpoint inhibitors (ICIs) have shown promising results in the treatment of ESCC. More than 20 phase II clinical trials have been launched to explore combinations of ICIs in the neoadjuvant setting for ESCC. Based on our phase II clinical trial, a two-arm phase III trial was launched in our Hospital. Methods: A two-arm phase III trial was launched in April 2020 in our Hospital. Patient recruitment will be completed within 18 months. The primary endpoint is event-free survival (EFS). The secondary endpoints include pathologic complete response (pCR), disease-free survival (DFS) rate, overall response rate (ORR), R0 resection rate, major pathologic response (MPR), adverse events (AEs), complication rate and quality of life (QOL). A biobank of pretreatment, resected tumor tissue and paired blood samples will be built for translational research in the future. Results: Until Dec. 2021, one hundred and twenty ESCC patients recruited in the trial. The trial is ongoing. Conclusion: This RCT directly compares NAC with neoadjuvant toripalimab plus chemotherapy in terms of EFS for locally advanced ESCC. The results may usher in a new era of resectable ESCC treatment.